2011
DOI: 10.5049/ebp.2011.9.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Blood Pressure Control and Left Ventricular Hypertrophy in Patients on Continuous Ambulatory Peritoneal Dialysis (CAPD) and Automated Peritoneal Dialysis (APD)

Abstract: This study aimed to investigate the influence of different peritoneal dialysis regimens on blood pressure control, the diurnal pattern of blood pressure and left ventricular hypertrophy in patients on peritoneal dialysis. Forty-four patients undergoing peritoneal dialysis were enrolled into the study. Patients were treated with different regimens of peritoneal dialysis: 26 patients on continuous ambulatory peritoneal dialysis (CAPD) and 18 patients on automated peritoneal dialysis (APD). All patients performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…Also in PD patients, Jang et al. pointed out a significant association of LVMI with SBP load . In hemodialysis patients, Rahman et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also in PD patients, Jang et al. pointed out a significant association of LVMI with SBP load . In hemodialysis patients, Rahman et al.…”
Section: Discussionmentioning
confidence: 99%
“…In the presented study, the study participants were clinically euvolemic and the mean BP values obtained from 24-h ambulatory measurements were similar for patients on both treatment modalities. At this point, there are inconsistent reports in the literature; some authors reported no difference between APD and CAPD modalities (3,12,13), while some reported higher BP measurements in patients on APD therapy due to earlier loss of residual renal function and lesser…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension and hypervolemia can result in an increase in the left ventricular (LV) afterload and may lead to an increase in LV wall thickness, although this condition alone fails to explain LV hypertrophy (LVH). Also, LVH is not always correlated with the severity of hypertension and hypervolemia in dialysis patients [3,12,13,14,15,16,17]. Another possible cause of LVH may be the increased cardiac output state produced by high-flow arteriovenous fistula, or anemia, as well as the direct effect of hyperparathyroidism [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies support the usefulness of circadian BP rhythm (a dipping pattern, morning BP) in predicting organ damage 18,19. Other studies show the usefulness of the BP load in predicting organ damage 6,7,20. In this present study, we obtained a similar correlation between the BP load and the LVMI.…”
Section: Discussionmentioning
confidence: 92%
“…The PTIN calculation is similar to the principle of the BP load calculation. Several studies have shown that the mean 24-hour BP did not correlate with the left ventricular mass index (LVMI); however, an increased BP load was associated with a higher LVMI 6,7…”
Section: Introductionmentioning
confidence: 99%